1992
DOI: 10.1093/sysbio/41.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for the Analysis of Comparative Data Using Phylogenetically Independent Contrasts

Abstract: We discuss and clarify several aspects of applying Felsenstein's (1985, Am. Nat. 125: 1-15) procedures to test for correlated evolution of continuous traits. This is one of several available comparative methods that maps data for phenotypic traits onto an existing phylogenetic tree (derived from independent information). Application of Felsenstein's method does not require an entirely dichotomous topology. It also does not require an assumption of gradual, clocklike character evolution, as might be modeled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2,333
2
11

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,063 publications
(2,350 citation statements)
references
References 35 publications
4
2,333
2
11
Order By: Relevance
“…As in my analysis of the data for 57 species, branch lengths in units of estimated divergence times yielded negative relationships in diagnostic plots of the absolute values of the standardized contrasts versus their standard deviations (Garland et al 1992). Such relationships can lead to inflated type I error rates (Díaz-Uriarte & Garland 1998).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…As in my analysis of the data for 57 species, branch lengths in units of estimated divergence times yielded negative relationships in diagnostic plots of the absolute values of the standardized contrasts versus their standard deviations (Garland et al 1992). Such relationships can lead to inflated type I error rates (Díaz-Uriarte & Garland 1998).…”
Section: Methodsmentioning
confidence: 88%
“…This is the best understood and most widely used of available phylogenetically based statistical methods (e.g. Losos 1990a, b;Harvey & Pagel 1991;Garland et al 1992Garland et al , 1999Garland & Adolph 1994;Irschick et al 1996;Martins 1996;Zani 1996;Díaz-Uriarte & Garland 1998) and was used in my previous analysis of endurance . I used the PDTREE program (available for free from the author; latest version 5.0 described in Garland et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Contrasts were generated using the PDAP:PDTree package (Garland et al, 1992) of the Mesquite computer program (Maddison and Maddison, 2005). The appropriateness of branch length estimations was then tested using CONTINUOUS (Pagel, 1994).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The likelihood ratio test revealed that the Null hypothesis of equal branch lengths should be rejected (ln-likelihood ratio = 75.09, df = 1, p = <0.0001). Independent contrasts were analyzed using least-squares regressions constrained to pass through the origin (Garland et al, 1992).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Our phylogenetic hypothesis was based on the conservative megatree, where unresolved nodes were included as soft politomies. We employed programs in the PDAP package (Garland et al, 1993) to transform the phylogenetic tree into a matrix of phylogenetic distances, and assessed whether the studied traits showed significant phylogenetic signal-i.e., the tendency of closely related species to resemble each other due to shared ancestryemploying the randomization procedure in the PHYSIG module developed by Blomberg et al (2003). This test consists in comparing the variance in phylogenetic independent contrasts observed in the real dataset against a null distribution obtained after the phenotypic data were randomized across the tips of the phylogeny (i.e., breaking any pattern of phylogenetic resemblance between relatives).…”
Section: Statistical and Phylogenetic Analysesmentioning
confidence: 99%